2014 24th International Conference on Field Programmable Logic and Applications (FPL) 2014
DOI: 10.1109/fpl.2014.6927428
|View full text |Cite
|
Sign up to set email alerts
|

A secure and unclonable embedded system using instruction-level PUF authentication

Abstract: In this paper we present a secure and unclonable embedded system design that can target either an FPGA or an ASIC technology. The premise of the security is that the executed machine code and the executing environment (the embedded processor) will authenticate each other at a per-instruction basis using Physical Unclonable Functions (PUFs) that are built into the processor. The PUFs ensure that the execution of the binary code may only proceed if the binary is compiled with the correct intrinsic knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In our case, such changes are easily detected during code enrollment phase. Also, the presence of LUT protects the PUF, post-programming, against modeling attacks as the responses are used as addresses to the LUT and do not directly correspond to the decoded opcode [8]. Code Injection Attack:From the point-of-view of software execution, an attacker might use code injection attack where a malicious instruction might be able to read out the internal data generated by a previously executed custom code instruction.…”
Section: E One Time Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, such changes are easily detected during code enrollment phase. Also, the presence of LUT protects the PUF, post-programming, against modeling attacks as the responses are used as addresses to the LUT and do not directly correspond to the decoded opcode [8]. Code Injection Attack:From the point-of-view of software execution, an attacker might use code injection attack where a malicious instruction might be able to read out the internal data generated by a previously executed custom code instruction.…”
Section: E One Time Accessibilitymentioning
confidence: 99%
“…We, re-encode part of the instruction set architecture depending on the hardware characteristics of each chip. Zheng et al propose a scheme similar to ours where they utilize PUFs for instruction obfuscation [8]. In their scheme, each instruction is stored in memory in two parts: the obfuscated instruction and a challenge word to the PUF device.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have shown that at the embedded system level, it is worthwhile to examine the system architecture and provide innovative solutions at the processor and memory management level. Zheng et al [28,29] shows how to prevent side-channel attacks (e.g., cache attack, timing attack) using the digital PUFs (Physical Unclonable Functions), applied in the authentication mechanism at the machine level as a digital fingerprint, thus protecting the embedded system from tampering. Research has also highlighted the importance of protecting the intellectual property (IP) and integrity of the hardware with more sophisticated countermeasures like IP watermarking [22].…”
Section: Related Workmentioning
confidence: 99%
“…As a proof of concept, we compare our arbiter PUF based MIPUF implemented using arbiter PUFs with regular FPGA-based arbiter PUFs implemented on five different FPGAs. The results are collected from Xilinx Spartan-6 XC6SLX45 platform using the implementation described in [11]. Figure 2a illustrate the probability distribution of the interconfi -guration variation of a MIPUF.…”
Section: Uniqueness and Reliabilitymentioning
confidence: 99%